Bioremediação na descontaminação de solo residual de basalto contaminado com óleo diesel e biodiesel - Meneghetti, Liliane Rebechi Ribeiro (2007)
The ground contamination caused by fuel leak is the one of subject in geoenvironmental researches area. These contaminated soil with petroleum hydrocarbons derived generate negative environment impacts, mainly because of the possibility of contaminating groundwater. The aim of this research was evaluate the decontamination of one residual soil from south Brazil contaminated with oil diesel and biodiesel, through the bioremediation techniques, such as: natural attenuation, bioaumentation and bioventing. The steps followed in development of the work were the physical-chemistry characterization of the soil, the microbiological analysis of the soil (microbiological quantification, selection of the bacteria for bioaumentation) evolution of CO2, determination of the amount of diesel e biodiesel with the soxlet method. The contaminate degradation by gaseous chromatography was carried out at the end of the experiment. For the bioremediation tests were molded cylindrical samples of residual soil with 10 cm of height and 7,5 cm of diameter. The variables analyzed were the microorganism population and the amount of oil diesel and biodiesel residual. The microbiological quantification was evaluated in 30, 60, 90 and 120 days after contamination. The samples were kept in the temperature and the humidity of the laboratoty and the pH was kept in accordance with natural soil and evaluated at the 30 and 120 days. It was observed the degradation of the pollutant in all techniques of the bioremediation studied, indicating that the native bacteria from the residual soil presented a high biodegradation potential